Mofdi Zakaria’s Poetic Revolutionary Discourse - Boumali, Hanane (Milev Journal of Research and Studies, 2019)
Revolution, without its people’s tongue to express it and elucidate its principles, is rootless and cannot exceed the surface of the ground on which it grows; therefore, it can be easily distorted and falsified because it did not go deeper into man’s affect nor did it blend with his mind and heart. No history records revolution; but, true poetry bestows upon the revolution what information fails to grant to history. Mofdi Zakaria is one of the Algerian poets who did not bind themselves to narrow patriotism determined by the identity card. He, however, concerned himself with his nation’s big issues, extolled its hopes, mourned its pains, was highly occupied with it, recorded it in his poems, and perhaps granted it a high status. This article would probably enlighten an important aspect of poeticism in Mofdi Zakaria’s revolutionary discourse via an interpretative approach to poetic texts in his book ‘The Sacred Flame’